Arterial and venous vascular complications in patients requiring peripheral venoarterial extracorporeal membrane oxygenation - Fisser, Christoph; Armbrüster, Corina; Wiest, Clemens; Philipp, Alois; Foltan, Maik; Lunz, Dirk; Pfister, Karin; Schneckenpointner, Roland; Schmid, Christof; Maier, Lars S.; Müller, Thomas; Lubnow, Matthias (Frontiers in Medicine, 2022)
Introduction: The aim of this study was to investigate the prevalence of arterial and venous complications in patients requiring peripheral veno-arterial extracorporeal membrane oxygenation (VA-ECMO) and its risk factors at time of cannulation as well as during ECMO support and to assess vascular complications in association with decannulation. Material and Methods: Between January 2010 to January 2020, of 1030 eligible VA-ECMO patients, 427 with analyzable vascular screening were included. Duplex sonography and/or CT-scan after decannulation were used to screen for thrombosis and pulmonary embolism as well as arterial complications. Near infrared spectrometry (NIRS) was established at time of cannulation and was continuously monitored during ECMO therapy. Results: The prevalence of venous complications was 27%. Thrombosis and pulmonary embolism were observed in 21% and 7%, respectively. Pulmonary embolism was more frequently diagnosed in patients with thrombosis (22% vs. 3%, p<0.001). In multivariate analysis risk factors for venous thrombosis were cannulation in the jugular vein compared to the femoral vein, but not anticoagulation. The prevalence of arterial complications was 37%, mainly ischemia followed by bleeding, dissection and compartment syndrome. Vascular surgery was necessary in 19% with 1% major amputations. A distal perfusion cannula (DPC) was implanted at cannulation in 24% patients and secondarily in 16% as required. In multivariate analysis risk factors for leg ischemia at time of cannulation were elevated D-Dimers, lower NIRS on the cannulated leg and lack of DPC. The best discriminative parameter was the difference of NIRS between the non-cannulated and the cannulated leg. In contrast, during ECMO support, only lack of DPC was associated with leg ischemia. A similar rate of complications associated with decannulation, mainly arterial thrombosis, ischemia, or bleeding, was seen with percutaneous and surgical approach (18% vs. 17%, p=0.295). Conclusion: VA-ECMO patients should be routinely screened for vascular complications. Decision to insert a DPC should be evaluated individually. However, NIRS monitoring of the cannulated and the non-cannulated leg is essential to identify legs at risk for critical ischemia. As complications associated with decannulation were equally distributed between percutaneous and surgical decannulation the applied method may be chosen according to local experience.